Understanding the types of racism and its effect on mental health among Muslim women in Victoria. Issue 2 (17th February 2023) - Yeasmeen, Tahira; Kelaher, Margaret; Brotherton, Julia M. L.
ABSTRACT: Background: Discrimination against racial and ethnic minority groups, especially the Muslim community, is more prevalent in Western countries and anti-Muslim belief, or Islamophobia, is also increasing around the world. Intersectionality of religion, race, and gender makes Muslim women vulnerable to racism. This study investigates different types of racism experienced by Muslim and non-Muslim women living in Victoria, Australia, and the adverse mental health outcome to them after experiencing racism. Method: Survey data were collected from 580 culturally and linguistically diverse (CALD) Victorian women from four local areas including both rural and urban communities. The survey asked about the participant's racism experience, types of racism, frequency of occurrence, and used the Kessler 6 Psychological Distress Scale to assess psychological distress after experiencing racism. The applied logistic regression analysis to assess the association between types of racism experiences and socio-demographic factors and to examine the impact of racism on individuals' psychological distress. Result: Muslim women, in general, had higher odds of experiencing racism (OR 1.70, 95% CI 1.02–2.83) than non-Muslim women, including types of racism such as being sworn at or verbally abused or exposed to offensive gestures (OR 1.78, 95% CI 1.11–2.85) and being told that they do not belong in Australia and should go back to their country (OR 1.61, 95% CI 1.00–2.58). Muslim women were more likely to be above the threshold for high or very high psychological distress than non-Muslim women, consistent across most types of racism. Conclusion: This study has found a higher prevalence of racism experienced by Muslim women compared to other ethnic minority groups and some types of racism are more likely to occur or be more toxic for Muslim women. Necessary intervention strategies should be implemented at every level of the society to raise awareness of and reduce exposure to racism among Muslim women.